Research on Simulation Technology in High and Low Orbit Hybrid Satellite Network - Zhihao WANG; Xiaoguang LANG; Shuangai XIAO (天地一体化信息网络)
By analyzed the characteristics of the space-integrated-ground information network,combined with the current development trend of advanced satellite network simulation technology at home and abroad,compared the advantages and disadvantages of current mainstream simulation software,a simulation platform based on QualNet was built.A solution for the space-integrated-ground information network simulation was proposed,the network topology,protocol model system and evaluation index system were designed,and the ability of the space-integrated-ground information network networking,routing and transmission was verifi ed.